(3QSGdI aj BOGH GdNWs
(3ChdgG (B:s
(3Yde GdNW eHOC GdYdhe GdJYdjejI bGd Gddg Ld LdGdI Yde HGdbde Yde GdGfSGf eGde jYde s
(3BNQgG (B:s
(3eMeO HMjK jMUd ef QCS ejeI hBNQ OGdg hejeI GdKdK GdhGbY ChdG jcJH s
(3Vef eLehY , JQJjHgG (B: (3GdJGSY hGdYTQhfs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1035 / 29) s
Keywords: (3GdeYGQa GdYGeIs